Consumer behavior towards telemarketing - Kharaishvili, Tinatin; Stříteský, Václav; Tahal, Radek, 1970-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
Telemarketing has become a big industry and convenient way of successfully managing business affairs with low costs. The aim of the thesis is to present telemarketing services from the customers point of view; analyzing what are consumer behavior towards telemarketing in Georgia and the Czech Republic, and also what are the perceptional and attitudinal causing factors of these behaviors. This is the comparative study and the research is mainly based on the primary data. For the research accomplishment, the questionnaire survey was used for gathering important information and data in order to make the relevant conclusions. According to the results, B2C telemarketing services are not welcomed in the Czech Republic and people tend to have mostly negative attitude. In case of Georgia, people have relatively more positive attitude and behavior towards telemarketing services.
Vedoucí práce: Václav Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses